Diretrizes e procedimentos para a implantação de transporte sob demanda compartilhado e complementar à rede convencional de transporte coletivo - Gustavo Wagner Nunes Balieiro (2022)
Considering that the conventional public transport system needs a change in the economic structure, alternatives are needed to reduce the inefficiencies and costs of the conventional system. For this, one of the alternatives is adopt a demand responsive transport (DRT). In this context, this dissertation presents the guidelines and procedures to enable the implementation of on-demand systems which are complementary to the conventional transport network. These guidelines go through the identification, treatment and relationship of data, evaluation of this on a BI tool (BI), creation of service areas and modeling the on-demand system in a simulation environment to obtain the performance of the system. Thus, it was possible to propose a specific model, a shared transport on demand, from the service area and supply structure of the conventional system. The method was applied in two cities, one large and the other medium-sized, with specific characteristics of the public transport offer. The procedure allowed the evaluation of the conventional system to identify the demand and frequency windows where it is convenient to replace the current system, in part or totally, with complementary transport on demand. The demand clustering, to define service areas, suggested an efficient system for both cities, since it is possible to identify specific similar behavior profiles for the adoption of the system. The guidelines for choosing the fleet, parameters and service area suggested that real performance, when correctly determined, tends to improve the quality of the services offered and overcome the deficiencies of conventional public transport.